To the last bullet : the inspiring story of braveheart, Ashok Kamte : 26/11 Mumbai terror attack - Cama Hospital incident unfolded-- - Kamte, Vinita; Deshmukh, Vinita (Pune : Ameya Prakashan, 2009)
Ashok Kamte, 1965-2008, former Additional Commissioner of Mumbai Police.
Keywords: Kamte, Ashok, -- 1965-2008.; Kamte, Vinita; Police -- India -- Mumbai -- Biography; Mumbai Terrorist Attacks, Mumbai, India, 2008.; Biographies